Relationship between early maladaptive schemas and personality traits with behavioral problems in students - Jafar Rahmanzadeh Moghadam; Galavizh Alizade; Mohammad Rostami (Ravānshināsī-i Afrād-i Istis̠nāyī, 2020)
Adolescents as one of the vulnerable age groups are exposed to a variety of psychological problems. The aim of present study was to investigate the relationship between early maladaptive schemas and personality traits with internalizing and externalizing behavioral problems. The present study is descriptive and correlational. In this study, 362 male high school students in Boukan city were selected using multi-stage cluster sampling method and completed the questionnaires of Behavioral Problems of Achenbach (1991), Schema Young (1998) and Neo short form (1992). Pearson correlation coefficient and multivariate regression were used to analyze the data. Regression analysis showed that 12% and 26% of the variance of internalizing behavioral problems and 15% and 20% of the variance of externalizing behavioral problems are due to early maladaptive schemas and personality traits in students, respectively. Early maladaptive schemas and personality traits have the potential to predict internalizing and externalizing behavioral problems in students. early maladaptive schemas and personality traits in students, respectively. Early maladaptive schemas and personality traits have the potential to predict internalizing and externalizing behavioral problems in students.